2010
DOI: 10.5194/bg-7-2369-2010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of total N <sub>2</sub> fixation rates in the ocean taking into account both the particulate and filtrate fractions

Abstract: Abstract. Using the 15 N 2 tracer method and high-sensitivity δ 15 N analytical systems, we determined N 2 fixation rates for ocean samples by dividing them into particulate (>0.7 µm) and filtrate (<0.7 µm) fractions. While N 2 fixation in the filtrate fraction had been ignored in previous studies, we found a significant N 2 fixation rates in the filtrate fraction in our study. The areal N 2 fixation rates in the western North Pacific Ocean estimated from the particulate fraction varied from <1 to 160 µmol N m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
3
42
1
Order By: Relevance
“…5). The overall range agrees well with previous field studies (Glibert and Bronk, 1994;Mulholland et al, 2006;Bonnet et al, 2016a;Konno et al, 2010;Benavides et al, 2013;Berthelot et al, 2015). Our data revealed that the fraction of DDN release to gross NF increased as light decreased (all p values < 0.05).…”
Section: Ddn Net Release To the Dissolved Poolsupporting
confidence: 82%
See 2 more Smart Citations
“…5). The overall range agrees well with previous field studies (Glibert and Bronk, 1994;Mulholland et al, 2006;Bonnet et al, 2016a;Konno et al, 2010;Benavides et al, 2013;Berthelot et al, 2015). Our data revealed that the fraction of DDN release to gross NF increased as light decreased (all p values < 0.05).…”
Section: Ddn Net Release To the Dissolved Poolsupporting
confidence: 82%
“…During the NF process, Trichodesmium release 10 to 50 % of the DD 15 N in the dissolved pool (Glibert and Bronk, 1994;Konno et al, 2010), primarily as dissolved organic N (DON, such as dissolved free amino acid) and NH + 4 (Capone et al, 1994;Mulholland et al, 2004). High DON and NH + 4 concentrations are often measured within Trichodesmium blooms (Karl et al, 1992;Lenes et al, 2001), being supportive of DDN release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…blooms in the Indian (Devassy et al, 1978(Devassy et al, , 1979Glibert and O'Neil, 1999), Pacific (Karl et al, 1992(Karl et al, , 1997b, and Atlantic (Lenes et al, 2001) oceans. Subsequent culture (Hutchins et al, 2007;Karl et al, 1992Karl et al, , 1997a) and field studies (Benavides et al, 2013b;Konno et al, 2010;Mulholland and Bernhardt, 2005) have quantified that diazotrophs release ∼ 50 % of the total fixed N 2 to the dissolved pool. Most of these studies were performed on the conspicuous Trichodesmium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Diazotrophs release part of the recently fixed N 2 as dissolved organic N (DON) and ammonium (NH + 4 ) in the dissolved pool (Glibert and Bronk, 1994;Mulholland et al, 2006). The magnitude of this release (10 to 80 %) is still under debate in the scientific community (Glibert and Bronk, 1994;Konno et al, 2010;Benavides et al, 2013b, a) and seems to depend on the physiological state of the cells (Berthelot et al, 2015a) as well as on exogenous factors such as viral lysis (Hewson et al, 2004) or sloppy feeding (O'Neil et al, 1996). Nevertheless, recent methods coupling 15 N 2 isotopic labeling, cell sorting by flow cytometry and high-resolution nanometer-scale secondary ion mass spectrometry (nanoSIMS) analyses enable the quantification of the DDN transfer from diazotrophs to specific groups of nondiazotrophic phytoplankton and bacteria, indicating that the DDN released in the dissolved pool is available and actively used by surrounding non-diazotrophic communities (Bonnet et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%